Magnetic inhomogeneities of soliton and breather type in magnetics with local nonhomogeneities of anisotropy - Ekomasov, E.G.; Azamatov, Sh.A.; Murtazin, R.R. (Functional Materials, 2008)
Using numerical methods, the peculiarities of domain wall transition through the two-dimensional region of magnetic anisotropy constant inhomogeneity has been considered. The origination and evolution of pulson type magnetic inhomogeneities localized in this region have been studied.